2016
DOI: 10.1080/17483107.2016.1177857
|View full text |Cite
|
Sign up to set email alerts
|

Wheeled mobility skills of wheelchair basketball players: a randomized controlled study

Abstract: Participation in regular wheelchair basketball sport may preserve and augment functional abilities in with wheelchair user Implications for rehabilitation The skills-sports relationship is reciprocal. With increased wheelchair skills, people may be more inclined to engage in sports; subsequently, with greater sports, wheelchair skills could improve. Wheelchair mobility skills during clinical rehabilitation should reflect the daily activities and needs of each wheelchair user. WST-Q provides advantages in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…This study has replicated and extended the work of Kilkens et al [16], by using the WST-Q rather than the Wheelchair Circuit as the measure of wheelchair skills and by studying experienced, community-dwelling wheelchair users rather than those undergoing inpatient rehabilitation. Our findings are also consistent with those of Saltan et al [29] who reported that WST-Q scores were higher in basketball players (who were probably fit) than nonplayers. We were able to corroborate our hypothesis that there are significant relationships between wheelchair skills scores and PO peak .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study has replicated and extended the work of Kilkens et al [16], by using the WST-Q rather than the Wheelchair Circuit as the measure of wheelchair skills and by studying experienced, community-dwelling wheelchair users rather than those undergoing inpatient rehabilitation. Our findings are also consistent with those of Saltan et al [29] who reported that WST-Q scores were higher in basketball players (who were probably fit) than nonplayers. We were able to corroborate our hypothesis that there are significant relationships between wheelchair skills scores and PO peak .…”
Section: Discussionsupporting
confidence: 93%
“…The overall goal of this study was to replicate and extend the work of Kilkens et al [16] by using the WST-Q (as Saltan et al [29] have done) rather than the Wheelchair Circuit as the measure of wheelchair skills and by studying experienced, community-dwelling wheelchair users rather than those undergoing inpatient rehabilitation. Our objective was to test the hypothesis that there are moderate relationships between the total WST-Q capacity, confidence, and performance scores and the PO peak values (as measured by a graded wheelchair exercise test on a motorized treadmill) of experienced, community-dwelling manual wheelchair users with SCI.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…4 Dahası, literatüre göre, eğitim düzeyi günlük yaşam aktiviteleri ve sosyal katılım fonksiyonlarını etkileyebilir. [7][8][9] Akçay ve ark.nın çalışmasında, engelli bireylerin aldıkları eğitimin yaşamlarını kolaylaştırmada etkili olduğu, engellinin ve ailesinin sosyo-kültürel düzeyinin, ulaşım ve erişilebilirliliğe ait düzenlemeleri etkilediğini bulmuşlardır. 10 Sporcuların eğitim ve çalışma oranlarının, kontrol grubuna göre yüksek olmasının, spor sayesinde kazanılan hareket etme becerisindeki artış ile ilişkili olduğunu düşünüyoruz.…”
Section: Discussionunclassified
“…İçerisinde yer alan baş üzerinden top atmayakalama, tekerlekli sandalye ile sağa-sola dönme, ileri geri sürme ve yerden top alma gibi aktiviteler günlük yaşam ile uyumludur (33). Elit TSB sporcularında yapılan bir çalışmada bireylerin en çok "geri geri tekerlekli sandalye sürme" ve "yürüyen merdivenden inip-çıkmada" zorlandıklarını belirtmişlerdir (23). Literatürde en çok zorlanılan becerilerin, 15 cm yüksekliğe çıkma, sabit tekerlek becerisi ve 10° eğimli rampa çıkma aktiviteleri olduğu belirlenmiştir (13,26,34…”
Section: Sonuçlarunclassified